Non verbal predication in Igbo (2014)
This paper discusses non-verbal predication in Igbo. Predication captures the process of complementation that exists in SVO languages. The theoretical framework adopted for the analysis is the Minimalist Program (MP) of linguistic theory. The study identifies non-verbal predicates as nominal, adverbial and prepositional predicates in Igbo. In Igbo different morphosyntactic and predication categories make use of different copulas. These copulas obligatorily occur in nonverbal predication structures. On the structural relations, the paper' assumes, following Bowers (2001), that the relation of predication is better expressed if there is a functional category Pr whose function is to relate the subject to the predicate. In Igbo, the Pro is null; it attracts the NP/AdvPIPP object to adjoin to it due to its strong affixal features forming a complex head (p\ pImerges with the subject to form the PrP. The computation continues to generate a proposition thus, providing a descriptively and explanatorily adequate structural analysis of nonverbal predication structures in Igbo.